Characteristic of pH and Temperature of Crude Extract of Glukoamilase from Gliocladium KE by using Solid Substrate of Sago Hampas - Risa Meutia Fiana; Novelina Novelina; Alfi Asben (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
This research wasaimed at figuring optimumpH and temperature of crude enzyme extract glukoamilase from isolate Gliocladium KEusing substrate of solid sago hampas. The research wasconducted by two phases, first wasfiguring optimumpH and second was optimum temperature. it wasbased on Complete Random Design. The data were statistically analyzed by using F test. If the result showedsignificance different,the analysis wascarried out by using Duncan’s New Multiple Range Test (DNMRT) with 5% tolerance. The result showedthat optimumpH ofcrude glukoamilaseextract from sago hampas was optimumpH of glukoamilasefrom Gliocladium KE using solid substrate of sago hampas waspH 6,0 with activity of enzyme 76,56 U/ml with final product of solube starch 0.09%, the level of reducing sugar 62,01%, and total sugar 78,43%. Optimum temperature was 60 ?C with enzyme activity 78,33 U/ml, final product of solube starch 0,13%, reducing sugar 63,04%, and total sugar 79,55%